MOBILISE-UTHM Resilient Tracker (RITTER) for resilient educational communities in Malaysia during the COVID-19 pandemic - Sulaiman, Noralfishah; Ismail, Maziah; Nazir, Umber; Abdul Latib, Siti Kursiah Kamalia; Muhammad Hafidz, Haridzah Fatihini; Mahmud, Nur Putri Najwa; Abid, Sheikh Kamran (IGI Global, 2022)
Coronavirus disease has caused a pandemic across the globe and it is now representing a significant threat to global health. Certainly, managing COVID-19 as compared to other types of disasters comes with a lot of unique challenges to many sectors including the educational sector, especially to higher education institutions(HEI). Since the announcement of movement control orders by the government of Malaysia, most of the Malaysia HEI students, including UTHM, have left their campuses, but the problems wrought by COVID-19 have not. UTHM employees from academic and supporting staff are also worried about their future for not continuously working as usual. The aim of the paper is to propose a disaster decision support system by combining UTHM Tracker and MOBILISE Digital System named MOBILISE-UTHM Resilient Tracker (RITTER) for UTHM students to build resilience during the COVID-19 outbreak and further to provide real-time intelligence for rapid disaster response combining UTHM Tracker and MOBILISE system for UTHM students during the COVID-19 outbreak in UTHM.